Inertia Optimization Control and Transient Stability Analysis of Wind Power Grid-Connected System - Song, Wenle; Wang, Lei; Zhao, Wei; Zhang, Xiangyu; Wang, Zhiwei (Frontiers in Energy Research, 2022)
Virtual inertia control effectively solves the low inertia caused by the grid connection of wind turbines with high permeability. To improve its engineering practicability, the influence of virtual inertia control on wind turbines' safety and the dynamic stability of grid-connection systems should be analyzed in detail. In this paper, the state equation of the wind power grid-connected system is established, and the influence of virtual inertia control on wind turbine shafting oscillation is analyzed based on the small-signal theory. Secondly, the nonlinear extended disturbance observer is designed as the compensation signal of inertia control to improve its dynamic stability. Based on the integral manifold method, the shafting model of the wind turbine is reduced, and the transient energy function of vertical shafting is established, which provided the basis for the design of the shafting stability controller. Finally, a grid-connected wind power system with high permeability is installed, and the results demonstrate that under the proposed control strategy, the swing stability of power angle is significantly improved, and the wind turbine shafting oscillation is suppressed.